Analysis of the Influence of Earning Per Share Ratio (EPS), Price Earning Ratio (P/E), and Price Book Value Ratio (PBV) to Stock Prices in the Technology Company Sub-Sector: Earning per Share (EPS), Price Earning Ratio (P/E), Price to Book Value (PBV), and Stock Price. - Munir, Anita; Kartanegara, Adam; Haikal, Fahri (Journal of Management and Leadership, 2025)
This study aims to examine the effect of profitability ratio (EPS), financial ratio (P/E), and market value ratio (PBV), on stock prices in the technology sub-sector listed on the IDX in 20019 - 2023. This research is a quantitative descriptive approach with the selected companies being LUCK, DIVA, NFCX, MCAS, KIOS, ATIC, MLPT, EMTK, PTSN, KREN, and MTDL. The analysis methods used are descriptive analysis, selection of panel data regression model estimates, classical assumption tests, and panel data regression tests. Hypothesis testing uses the t-test to test the coefficient partially, the f-test to test the magnitude of the variable effect, and the Coefficient of Determination test using R2to test simultaneously. All variables have been tested using the classical assumption test. The results showed that all variables passed the classical assumption test and panel data regression test, so they were suitable for use as research data. The statistical t test results show that the variable earning per share ratio (EPS) partially has a significant and positive effect on stock prices. The price earning ratio (P/E) variable partially has a significant and positive effect on stock prices. The price to book value (PBV) ratio variable partially has a significant and negative effect on stock prices. Simultaneously, the Earning per Share (EPS), Price Earning Ratio (P/E), and Price to Book Value (PBV) ratios have a significant effect on stock prices. This is explained by the Sig F value = 0.000 < Level of Significant = 0.05, and the R2 (coefficient of determination) value of 91.702%, while other factors outside the model explain the remaining 8.298%. This research can be used by companies and investors who will make investments